What is the nature and function of Spatio-Temporal Imagination?: can it plausibly be explained as an offline simulation of the visual process? - King, Peter R. (2010)
The main aim of this thesis is to analyse the nature and function of Spatio-Temporal Imagination (STIm) under an imagination-as-simulation framework. STIm is defined as any imaginative act that allows you to consider a location and/or a time other than the one you are currently experiencing. I will focus on the phenomenal visual imagery aspect of this mental phenomenon and hence will not discuss other potential versions of STIm in any detail.